Bilateral multidirectional jumps with reactive jump-landings achieve osteogenic thresholds with and without instruction in premenopausal women. (March 2020) - Clissold, Tracey L.; Cronin, John B.; De Souza, Mary Jane; Wilson, Daniel; Winwood, Paul W.
Abstract: Background: Currently jump-landing ground reaction forces have only been quantified in the vertical direction as a stimulus for bone development. This study quantified the full-spectrum of jump-landing force magnitudes (body weight's) and rates of strain (body weights per second) of bilateral multidirectional jumps (star jump and stride jump) with reactive jump-landings (i.e. jumping immediately after initial jump-landing) among premenopausal women. It was also of interest to quantify the influence of instruction on the magnitude and rate of the jump-landing ground reaction forces. Methods: Twenty-one women [Mean (SD): 43.3(5.9)yr; 69.4(9.6)kg; 167(5.5)cm; 27.5(8.7)% body fat] performed a jump testing session 'with instruction' followed by a jump testing session performed one week later with 'instruction withdrawn'. Findings: The resultant magnitudes (3.90 to 5.38, body weights) and rates of strain (192 to 329, body weights per second) for the jump-landings, performed on a force plate, exceeded previously determined osteogenic thresholds (>3body weight's and >43body weights per second, respectively). An instruction effect was observed for resultant (↑8% and ↑12%; P  ≤ .01) and vertical (↑8% and ↑7%; P  ≤ .01) ground reaction force's (Newtons and body weight, respectively) indicating learning/practice effects for these exercises. A jump-landing effect was observed, with larger peak rates of strain (↑29%; P  < .0001, body weight per second) and peak forces (↑12% to ↑48%; P  ≤ .01, body weights) for the second jump-landing (post-reactive jump). Interpretation: These multidirectional bilateral jumps represent a unique training stimulus for premenopausal women and achieve osteogenic thresholds thought pre-requisite for bone growth and could be utilized in the development of osteogenic exercise programs. Highlights: Magnitudes and rates of strain for star and stride jump-landings exceeded osteogenic thresholds. Landing forces increased after one instructed practice session indicating a learning effect. Larger forces found for second jump-landing (jumping immediately after initial jump-landing). Medio-lateral landing forces substantially greater in the star jump compared with the stride jump. Anterio-posterior landing forces markedly greater in the stride jump compared with the star jump.